Endoscopic direct diverticulitis therapy for acute uncomplicated diverticulitis - Ren, Jian-Zhen; Cai, Jun; Li, Bo; Yang, Guang; Liao, Su-Huan; Chen, Jia-Kuan; Guo, Yi-Tian; Lu, Yang-Bor; Huang, Si-Lin (Endoscopy, 2025)
The global prevalence of acute uncomplicated diverticulitis is increasing, and patient care for this condition is experiencing a paradigm shift. This study evaluated the diagnostic and therapeutic value of endoscopic direct diverticulitis therapy (EDDT) using cholangioscope-assisted colonoscopy for acute uncomplicated diverticulitis.Patients with computed tomography-confirmed acute uncomplicated diverticulitis (Hinchey stage Ia or Ib) who underwent EDDT between July 2023 and December 2024 were included. The technical success rate of EDDT, procedure time, endoscopic findings, symptom resolution, and recurrence were documented.12 patients (mean age 45.2 [SD 10.1] years, 10 males) underwent EDDT. Technical success was achieved in all 12 patients (100%). Cholangioscope-assisted colonoscopy revealed fecaliths with pus in seven patients, copious purulent collection in four, edematous inflammatory mucosa in five, and bleeding in one. Corresponding treatments were applied without complications. Abdominal pain resolved immediately after EDDT, and inflammatory parameters returned to normal. No recurrences were reported over a mean follow-up of 4 months (range 1–10 months).EDDT utilizing cholangioscope-assisted colonoscopy was a feasible alternative treatment for acute uncomplicated diverticulitis, offering diagnostic and therapeutic advantages through direct visualization. Although preliminary results are promising, further studies with larger cohorts are warranted to confirm its efficacy and long-term outcomes.